Choroidal Detachment in Idiopathic CD4 Lymphocytopenia - Avadhesh Oli; Raja Narayanan; INHS Asvini; Navy Nagar; Colaba; Smt Kanuri Santhamma (Delhi Journal of Ophthalmology)
Usually reduction in CD4 cell count is seen with HIV infection, however CD4 lymphocytopenia in absence of HIV infection is called as Idiopathic CD4 Lymphocytopenia (ICL). The patients usually present with features of immunosuppression and opportunistic infections. Ophthalmic manifestations of this rare entity are not well known and very few cases are reported till date. We present a case of a 69 year old male patient who reported with profound reduction in his visual acuity in his left eye for 15 days. On examination of his left eye the visual acuity was hand motion close to face and he had 360 degree choroidal detachment which was confirmed on a B scan. He had evidence of subretinal fluid on optical coherence tomography (OCT). His detailed uveitis workup was unremarkable and HIV test was negative twice repeated at two occasions six weeks apart. His CD4 count was 57 cells/mm3 with all other investigations normal. This report highlights that iIdiopathic CD4 lymphocytopenia is a rare entity which usually presents as opportunistic infections as reported in the literature. This case of ICL had choroidal detachment which is unusual presentation of this rare entity.